The Relationships of Dust and Total Masses of Luminous Infrared Galaxies with Their Far Infrared and Total Luminosities Using Two Methods of Distance Measurements - Shaker, Farah Z.; Al Najm, M. N. (Iraqi Journal of Science, 2024)
This research aims to determine the nature of the relationships among luminous infrared galaxies (LIRGs) by using different methods of distance measurement (distance modulus “dm” and luminosity distance “dl”). We used data from the following sources: NASA Extragalactic Database (NED) and the HYPERLEDA database, where this data was used to study the nature of the relationships and the extent to which they relate to each other. The program (statistica-win-program) was employed, which helped us know the strength of the association between the variables. The results of the statistical analysis showed that there was a strong correlation between dust mass (Mdust dm & Mdust dl) and luminous infrared (LFIRdm, LIRdm) & (LFIRdl, LIRdl), where the partial correlation coefficient was equal to (R⋍0.7) and the slope was linear. There was also a positive correlation between (LFIRdm, LFIRdl)& ( ) where the partial correlation coefficient was (R⋍0.4) with a linear slope. The relationship between (LIR)& ( ) was a positive relation in the modulus distance case (dm), where its correlation was equal to (R⋍0.4), but in another case (luminosity distance), the relation was very weak, and the correlation was (R⋍0.2). The relationship between total masses ( ) & (LFIRdm, dl) in both cases of distance (dm) & (dl) was good, and the partial correlation coefficient was equal to (R⋍0.4) with a linear slope. The relationship between (LIR) & ( ) in both cases of distance was also positive, and the partial correlation coefficient was equal to (R⋍0.3). There was an inverse relationship between the ratio fluxes (F100/F60) & ( ), as well as a very tight partial correlation coefficient, which was equal to (R⋍-0.9) with a slope of (-1).